Presentations for the event on supply chain management in construction held on Wednesday, 14 April 1999 at the Institution of Civil Engineers, London (Institution of Civil Engineers, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held in 1999.